Ethical Issues in the Assessment of Speaking Skills - Metruk, Rastislav (Communications - Scientific letters of the University of Zilina, 2018)
Language assessment is a rather complex yet an inseparable part of the learning process. Not only should it represent learners’ achievements, but it also ought to facilitate and enhance learning. Assessing spoken proficiency can be regarded as particularly difficult, complex, and time-consuming since many aspects of oral performance need to be carefully considered. The two types of assessment, the assessment for learning (formative assessment) and the assessment of learning (summative assessment), have to be taken into account as they both occupy a significant role in the overall development of speaking skills of a learner. However, mastering the formal and informal kinds of assessment requires considerable expertise, hard effort, and invaluable experience. Therefore, EFL teachers often fail in their attempt to conduct a proper and fair assessment of speaking skills. Moreover, the question of ethics, which represents an important element of the assessment process, is frequently neglected too. This paper discusses ethical issues in the assessment of spoken proficiency of EFL learners. Furthermore, ethical obligations EFL teachers ought to comply with in terms of the Communicative approach are also explored.